Anatomical variations of intra-sphenoid sinus septations in a sample of Kashmiri population: a non-contrast computed tomography study - Wani, Abdul Haseeb; Shiekh, Yassar; Parry, Arshed Hussain; Qayoom, Zahid (International Journal of Research in Medical Sciences, 2019)
Background: The sphenoid sinus shows multitude of variations in pneumatization, size and pattern of septations leading to differences in its segmentation. Pre-operative knowledge of their attachment especially to posterolateral bony walls covering vital structures is of utmost importance for a safe trans-sphenoidal approach for various surgical procedures involving skull base. Non-contrast computed tomography (NCCT) with its ability to provide multiplanar reformations (MPR) with sharp algorithms is now a reference standard for visualization of these intra-sphenoid sinus septations preoperatively. The objective of this study was to determine the number and attachment of intra-sphenoid sinus septations in a Kashmiri population sample. Methods: NCCT head images of 591 patients in the age range of 16 to 75 years were analyzed retrospectively. Individuals with age less than 16 years, previous surgery involving skull base/sphenoid sinus, trauma causing hem sinus/fractures around skull base or having space occupying lesions around skull base/sphenoid sinus were excluded from the study. On the CT workstation multi-planar coronal, sagittal and axial reconstructions were performed and subsequently examined. Results: The age range was 16 to 75 years with mean age of 43.56 years of which 453 (76.6%) were males and 138 (23.4%) were females. Single intra-sphenoid septation was the most common anatomic variant in present study (79.7%) being complete in 71.7% and partial or incomplete in 8% of the examined subjects. Double septa were found in 11% inpresent study and more than 2 septae in 3.4%. After sellar attachment (51%) the next most common site of attachment was to the carotid canal (29.5%) (23% to left ICA and 6.5% to the right ICA). Conclusions: Intricate knowledge about sphenoid sinus, its pneumatization and anatomical variations in intra-sphenoid sinus septations and its relationship with the surrounding vital structures is of utmost importance before performing any endoscopic/open surgery involving skull base via trans-sphenoidal approach. The present study shows that a significant percentage of septal attachment to the carotid canal makes main sphenoidal septum as not so reliable landmark for endoscopic procedures as used to be in the pre-imaging era. Thus, preoperative CT is mandatory to avoid injuries to para-sellar neurovascular and glandular structures.